Features of energy saving potential in household evaluation - Zaneta Simanaviciene; Andzej Volochovic; Akvile Cibinskiene (Institute of Economic Research (IER), 2015)
Scientists from all over the world recognize that energy saving in households is currently very relevant topic. Energy resources are very important factor for each country's economic vitality. Not only the country's replenishment in energy resources is important, but also the reduction of energy consumption volume.
Keywords: Q43; Q51; Q56; C92; D1; 330; energy saving potential; households; evaluation; behavior change